Interval training has more negative effects on sleep in adolescent speed skaters: a randomized cross controlled trial - Kong, Zhenxing; Wei, Xinhua; Shen, Meng; Cheng, Yue; Feng, Junpeng (Frontiers in Sports and Active Living, 2024)
Objective: Sleep is an essential component of athletic performance and recovery. This study aimed to investigate the effects of different types of high-intensity exercise on sleep parameters in adolescent speed skaters. Methods: Eighteen male adolescent speed skaters underwent aerobic capacity testing, Wingate testing, and interval training in a randomized crossover design to assess strength output, heart rate, and blood lactate levels during exercise. Sleep quality after each type of exercise was evaluated using the Firstbeat Bodyguard 3 monitor.Results: The results showed that Wingate testing and interval training led to decreased sleep duration, increased duration of stress, decreased RMSSD, and increased LF/HF ratio (p<0.01). Conversely, aerobic capacity testing did not significantly affect sleep (p>0.05). The impact of interval training on sleep parameters was more significant compared to aerobic capacity testing (p<0.01) and Wingate testing (p<0.01). Conclusion: High-intensity anaerobic exercise has a profound impact on athletes' sleep, primarily resulting in decreased sleep duration, increased stress duration, decreased RMSSD, and increased LF/HF ratio.